Salinomycin Modulates the Expression of mRNAs and miRNAs Related to Stemness in Endometrial Cancer - Talkowski, Karol; KieŦ#130;basiŦ#132;ski, Kamil; Peszek, Wojciech; Grabarek, Beniamin O.; BoroŦ#132, Dariusz; Oplawski, Marcin (Current Pharmaceutical Biotechnology, 2021)
Background: Salinomycin, an ionophore antibiotic, has a strong anti-cancer effect, inducing the apoptosis of cancer cells and cancer stem cells. Objective: The aim of the study was to assess the influence of salinomycin on the expression profile of genes related to stemness and miRNA regulating their expression in endometrial cancer cells. Methods: Endometrial cancer cells of cell line Ishikawa were exposed to salinomycin at concentrations in the range of 0.1-100 μM, with the aim of determining its pro-apoptotic potential and the concentration which would cause the death of 50% of the cells (Sulforhodamine B test). In the following stages, the cells were incubated with the drug at a concentration of 1μM for 12,24 and 48 hour periods and compared to the control. Determining the changes in the expression of the genes related to stemness and regulating their miRNA was done using the microarray technique and RTqPCR. ELISA assay was performed in order to determine the level of TGFβ2, COL14A1, CDH2, WNT5A in cell culture under salinomycin treatment in comparison to the control. Results: Salinomycin caused the apoptosis of cells. For the concentration of 0.1 μM, a decrease in the population of living cells by 11.9% was determined. For 1 μM, it was 49.8%, for 10 μM -69.4%, and for a concentration of 100 μM - 87.9%. The most noticeable changes in the expression caused by the addition of salinomycin into the culture were noted for mRNA: TGFβ2; WNT5A (up-regulated); COL14A1; CDH2 (down-regulated), as well as miRNA: hsa-miR-411 (up-regulated); hsa-miR-200a; hsa-miR-33a; hsa-miR-199a; hsa-miR-371-5p; hsa-miR-374; hsa-miR-374b (down-regulated). Conclusion: It was confirmed that salinomycin has an influence on the stemness process. The most noticeable changes in the expression were noted for mRNA: TGFβ2; COL14A1; CDH2; WNT5A, as well as for miRNA: hsa-miR-200a; hsa-miR-33a; hsa-miR-199a; hsa-miR-371-5p; hsa-miR-411; hsa-miR- 374a; hsa-miR-374b.
Keywords: microarray